Implementasi Program the Duke of Edinburgh International Award untuk Menumbuhkan Sikap Kemandirian dan Kepercayaan Diri Siswa SMP Progresif Bumi Shalawat - Suherman Suherman; Kaniati Amalia; I Ketut Atmaja Johny Artha; Amrozi Khamidi; Mochamad Nursalim (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to examine the effectiveness of The Duke of Edinburgh’s International Award (DofE) program in developing students’ independence and self-confidence through a literature review approach. The method used is a literature review of a number of relevant previous studies, both quantitative, qualitative, and social impact reports from the implementation of the DofE program in various countries. The results of the study indicate that the DofE program consistently provides a positive contribution to strengthening the character of participants, especially in aspects of mental resilience, leadership, 21st century skills, and social engagement. Various studies have concluded that the experience-based activities in this program are effective in increasing students’ self-confidence and independence, and have an impact on improving academic achievement and mental health. Therefore, the implementation of DofE in the Indonesian educational environment, such as at SMP Progresif Bumi Shalawat, is considered strategic as part of strengthening character education and the readiness of the younger generation to face future challenges. Keywords: Independence, Self-Confidence, Literature Review, Character Education